2012
DOI: 10.1128/jvi.05899-11
|View full text |Cite
|
Sign up to set email alerts
|

Measles Virus C Protein Interferes with Beta Interferon Transcription in the Nucleus

Abstract: Transcriptional induction of beta interferon (IFN-␤) through pattern recognition receptors is a key event in the host defense against invading viruses. Infection of cells by paramyxoviruses, like measles virus (MV) (genus Morbillivirus), is sensed predominantly by the ubiquitous cytoplasmic helicase RIG-I, recognizing viral 5=-triphosphate RNAs, and to some degree by MDA5. While MDA5 activation is effectively prevented by the MV V protein, the viral mechanisms for inhibition of MDA5-independent induction of IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 76 publications
1
55
0
Order By: Relevance
“…Closer to RVFV, the NSs protein of Bunyamwera virus (26) and of La Crosse virus (45) also display nuclear distributions. Interestingly, it has been recently reported that the capacity of the C protein of the measles virus to inhibit IFN-␤ gene expression requires the nuclear localization of the viral protein (43).…”
Section: Discussionmentioning
confidence: 99%
“…Closer to RVFV, the NSs protein of Bunyamwera virus (26) and of La Crosse virus (45) also display nuclear distributions. Interestingly, it has been recently reported that the capacity of the C protein of the measles virus to inhibit IFN-␤ gene expression requires the nuclear localization of the viral protein (43).…”
Section: Discussionmentioning
confidence: 99%
“…This model is consistent with the reported importance of NiV W protein nuclear localisation to its inhibition of TLR3-dependent IFN induction [82] . MeV C protein also inhibits IFN induction, correlating with its nuclear localisation [83] , although MeV C does not affect IRF-3 directly, and appears to have an undetermined nuclear target [83] . By contrast, cytoplasmic NDV and SeV V protein bind directly to IRF-3, thereby preventing its nuclear translocation [76] .…”
Section: Inhibition Of Irf-3 Activationmentioning
confidence: 97%
“…Since the C protein downregulates viral RNA synthesis (12,15,16), it was proposed that the C protein allows the virus to escape detection by the cytosolic RNA sensors retinoic acid-inducible gene I (RIG-I) and MDA5 and prevents IFN production (12). A recent study reported that the transfected C protein can interfere with IFN-␤ transcription in the nucleus (17). It remains to be determined whether this occurs in infected cells.…”
mentioning
confidence: 99%